Theory and practice of ethnography : readings from the periphery - Kasi, Eswarappa; Malik, Ramesh C.; Indirā Gāndhī Rāshṭrīya Mānava Saṅgrahālaya; University of Hyderabad. School of Humanities; University of Hyderabad. School of Social Sciences (Indira Gandhi Rashtriya Manav Sangrahalaya ; Rawat Publications, 2009)
Contributed articles presented at an international conference organized by School of Humanities and School of Social Science, University of Hyderabad in July 3-5, 2007.
Keywords: Ethnographic Discourse of the Other : an International Conference : (Hyderabad, India : : 2007); Ethnology : Congresses; etniset ryhmät; etniset vähemmistöt; etnografia; heimot; indoarjalaiset kielet; kansalaistoiminta; kansantarinat; kaunokirjallisuus; maanviljely; orijan kieli; paikallisyhteisöt; sosiaalinen kestävyys; sosiaalinen muutos; yhteiskunnallinen asema; etniska grupper; etniska minoriteter; etnografi; stammar (folkgrupper); indoariska språk; medborgaraktivitet; folksägner; skönlitteratur; jordbruk; oriya; lokalsamhällen; social hållbarhet; social förändring; samhällsställning; Andhra Pradesh; Bastar; Bhopal; Intia; Bangladesh; Kerala; Indien; rongmeit